Carbon emission reductions, pricing and social welfare of three-echelon supply chain considering consumer environmental awareness under carbon tax policy - Zhang, Yunfeng; Qin, Ying (Frontiers in Environmental Science, 2022)
With the rapid growth in carbon emissions from transport, reducing these emissions is becoming as important as reducing emissions from production. We took a transporter as a member of the supply chain system and constructed a three-echelon supply chain composed of a manufacturer, transporter, and retailer. This study applies the Stackelberg game and Nash game to study the optimal carbon emission reductions, pricing, and social welfare when the government imposes a carbon tax on carbon emitters and consumers are environmentally conscious. The four scenarios were designed as follows:(1) non-cooperative decision-making (NN model), in which neither carbon emission reduction cooperation nor pricing cooperation takes place; (2) local-cooperative decision-making Ⅰ (CN model), in which only cooperation in the field of carbon emission reductions takes place; (3) local-cooperative decision-making Ⅱ (NC model), in which cooperation in the field of pricing without cooperation in the area of carbon emission reductions takes place; and (4) overall-cooperative decision-making (CC model), in which both cooperation in the field of carbon emission reductions and cooperation in the area of pricing take place. The results show that economic (as profit of the supply chain system), social (as pricing and social welfare), and environmental benefits (as the optimal carbon emission reductions) for the three-echelon supply chain will improve with the deepening of cooperation among the supply chain members. A cross-shareholding contract is designed to coordinate the supply chain and achieve the optimal state of the overall cooperative decision. Finally, the paper provides suggestions on carbon emission reductions for enterprises and policymaking for the government.